ISLAMIC SOCIAL FINANCE DIGITALIZATION AND SUSTAINABLE DEVELOPMENT GOALS: THE MEDIATING ROLE OF GOVERNANCE TRANSPARENCY - padlim hanif; Yosy Arisandy (UNIB Press, 2026)
Islamic social finance instruments, particularly zakat and waqf, have long been regarded as strategic mechanisms for poverty alleviation and social welfare, positioning them as natural contributors to the achievement of the Sustainable Development Goals (SDGs). In recent years, zakat and waqf institutions across Indonesia and other Muslim-majority countries have undergone rapid digitalization, including online collection platforms, digital reporting dashboards, and blockchain-based fund tracking. However, evidence suggests that digitalization alone does not automatically strengthen donors' (muzakki and waqif) trust or the institutional legitimacy required for Islamic social finance to meaningfully contribute to the SDGs, raising questions about the mechanisms through which digital transformation translates into developmental impact. This study examines the effect of Digital Transformation of Islamic social finance institutions on their contribution to SDGs achievement, with Governance Transparency and Accountability as a mediating variable. This study employs a quantitative explanatory survey design involving 190 respondents comprising managers and officers of zakat and waqf institutions, selected through purposive sampling. Data were analyzed using IBM SPSS Statistics through validity testing, reliability testing, classical assumption testing, multiple linear regression, and mediation analysis using the causal-steps approach complemented by the Sobel test. The results indicate that Digital Transformation has a positive and significant effect on both Governance Transparency and SDGs Contribution, Governance Transparency positively affects SDGs Contribution, and Governance Transparency partially mediates the effect of Digital Transformation on SDGs Contribution. These findings extend Maqasid al-Shariah Theory and Institutional Theory, and offer practical implications for zakat and waqf authorities, including Indonesia's National Zakat Agency (BAZNAS) and waqf regulatory bodies, in strengthening governance transparency as a strategic complement to digital transformation.